Practice-Based Interventions Addressing Concomitant Depression and Chronic Medical Conditions in the Primary Care Setting: A Systematic Review and Meta-Analysis. (October 2013) - Watson, Lea C.; Amick, Halle R.; Gaynes, Bradley N.; Brownley, Kimberly A.; Thaker, Samruddhi; Viswanathan, Meera; Jonas, Daniel E.
Background: Depression concomitant with chronic medical conditions is common and burdensome in primary care.Objective: To assess the effectiveness of practice-based interventions for improving depression and chronic medical outcomes.Data Sources: MEDLINE, Embase, the Cochrane Library, CINAHL, and PsycINFO from inception to June 11, 2012.Study Selection, Appraisal, and Synthesis: Two reviewers independently selected, extracted data from, and rated the quality of trials and systematic reviews. Strength of evidence (SOE) was graded using established criteria.Results: Twenty-four published articles reported data from 12 studies, all at least 6 months long. All studies compared a form of collaborative care with usual or enhanced usual care. Studies evaluated adults with arthritis, cancer, diabetes, heart disease, HIV, or multiple medical conditions. Meta-analyses found that intervention recipients achieved greater improvement than controls in depression symptoms, response, remission, and depression-free days (moderate SOE); satisfaction with care (moderate SOE); and quality of life (moderate SOE). Few data were available on outcomes for chronic medical conditions. Meta-analyses revealed that patients with diabetes receiving collaborative care exhibited no difference in diabetes control compared with control groups (change in HbA1c: weighted mean difference 0.13, 95% confidence interval = −0.22 to 0.48 at 6 months; 0.24, 95% confidence interval = −0.14 to 0.62 at 12 months; low SOE). The only study to use HbA1c as a predefined outcome measure and a "treat-to-target" intervention for diabetes as well as depression, TEAMcare, reported significant reductions in HbA1c (7.42 vs 7.87 at 6 months; 7.33 vs 7.81 at 12 months; overall P < .001).Limitations: Few relevant trials reported on medical outcomes.Conclusions: Collaborative care interventions improved outcomes for depression and quality of life in primary care patients with varying medical conditions. Few data were available on medical outcomes. Future studies of concomitant depression and chronic medical conditions should consider measures of medical outcomes as primary outcomes.